POLIGAMI DAN POWER EKONOMI - Dakhoir, Ahmad (AL-QARDH, 2016)
The motive of polygamy in Indonesia is very diverse. Public perception against one of the motives of polygamy is very strong due to economic problems. Economic motives as power for of polygamy is not always right.This paper mainstreem denied the presumption that of polygamy carried out by economic forces. In short those who practice polygamy only potentially be implemented for the rich or the elite tier of other groups.Theoretically-normatively basic theory which became one of the parameters can be polygamous in Indonesia, namely the existence of evidence of the husband‟s income would be polygamous is a figure that could provide for the economy to all the wives and children. The result is that a strong economic motive is considered the basis for of polygamy was not entirely right.In Surabaya, for example secretly polygamous husband of 64 polygamous marriages procedural was only earning less than Rp. 17 million. Of these 39% are self-employed husband by profession who earn no more than 2.5 million per month, and 31.3% earn Rp. 4.9 million.While polygamous husband in secret of 56 polygamous marriages only income below 24 million. Of these the most that 50% are self-employed husband by profession who earn no more than 2.4 million every month